The Influence of Work Environment and Workload on the Performance of Production Department Employees at CV. Tirto Agung Rejoso Pasuruan - Al Kahfi, Mufarrij; Irbayuni, Sulastri (PT Inovasi Pratama Internasional, 2024)
Using the CV research object, the purpose of this study is to elucidate how workload and work environment affect employee performance. Rejoso Tirto Agung Pasuruan A quantitative methodology is used in this study. Employees of CV made up the study's population. Rejoso Tirto Agung Pasuruan. Forty responders from CV's production division served as the study's sample in the meanwhile. Rejoso Tirto Agung Pasuruan. Using the SmartPLS program, all tests demonstrate that all tests receive scores higher than the required values, indicating that the test is deemed trustworthy. This study employs a quantitative research design, PLS analysis, and descriptive statistics for data analysis. The findings of the study indicate that the workload is unable to improve CV workers' performance. Tirto Agung Rejoso Pasuruan, however CV personnel' performance might be encouraged by their work environment. Pasuruan Tirto Agung Rejoso.